A Dual System of Justice: Financial Institutions and White-Collar Criminal Enforcement - Bellm, Sebastian (2021)
Proposing more severe punishment for white-collar criminals is not a new concept. While many argue for the increased prison time of white-collar offenders, others provide “a counter-perspective on the use of prison sentences.” Other areas of academic publication support the convergence of sentencing guidelines for white-collar and drug-related criminals, particularly in light of utilitarian and retributivist principles. Rather than simply recommending that white-collar criminals should be punished more, this Note proposes two distinct structural solutions that reevaluate the current policies directing the punishment of white-collar criminal conduct. Specifically, this Note argues that the Department of Justice (DOJ) should reconsider the practice of levying large fines against corporate entities that, through their public structure, pass the fines on to innocent shareholders. After evaluating how and why the current approaches to the enforcement of white-collar laws are insufficient and fail to meet the fundamental principles of punishment, this Note proposes two solutions. First, FinCEN, the government organization tasked with combatting financial crimes and money laundering, should develop a more thorough and holistic approach to the reporting requirements of financial institutions. Second, judges should become more involved in the approval of Deferred Prosecution Agreements (DPAs). Rather than viewing DPAs as only bilateral agreements between prosecutors and defendants, judges should serve as the representatives of public interest, similar to their role in plea agreements. These two proposals would strengthen the overall response to corporate white-collar crime by deterring future criminal activity